Protective role of omega 3 on histological status of liver of albino rats affected by energy drinks - Aslam, Imtiaz; Rasheed, Ammara; Jafri, Farhana; Tafweez, Raafea; Munira, Mahjabeen (Journal of Fatima Jinnah Medical University, 2022)
Background: This study was planned to see the toxic effects of energy drinks on the liver. The study was done for a period of one month in the animal house of the postgraduate medical institute, Lahore, on albino rats. Omega 3 was selected as a protective agent against the toxicity of energy drinks on liver parenchyma. The purpose of this study was to evaluate the protective role of omega 3 on the histology of liver parenchyma damaged by an energy drink. Subjects and methods: A total of 30 male adult albino rats were used in this experimental study. They were divided into three groups with 10 animals in each: Group 1 was treated with distilled water at the dose of 0.5ml/100g of body weight, Group 2 was given an energy drink at the dose of 1.5ml/100g of body weight and Group 3 at the dose of 0.04-0.05ml/100g of omega 3 and 1.5ml/100g of body weight of energy drink. All doses were given for 4 weeks, orally once daily. Results: Hepatotoxicity was produced by the energy drink, as histological parameters deranged in experimental group 2, which was treated with the energy drink alone. While group 3, which was treated with omega 3 along with energy drink showed the protection of hepatic architecture to some extent by reducing inflammation and nuclear changes to prove the protective role of omega 3. Conclusion: Energy drink when given at dose of dose was 1.5ml/100gram/body wt.1.8ml was average dose adjusted on average base for a period of one month causes hepatotoxicity in albino rats. Omega 3 was given as at dose of 0.04-0.05ml/100 gm of body weight/day for a period of one month. It is concluded that 0.04-0.05ml/100mg of b.w/day of Omega 3 offered partial protection to liver against damage by energy drinks. Conclusion: It is concluded that 0.04-0.05ml/100mg of b.w/day of Omega 3 offered partial protection to the liver against damage by energy drinks.